Design and Analyses of Direct Conversion RF Receiver for WLAN System based on IEEE 802.11a Standard - A. A., Abd Aziz; N. A., Shairi; M.I., Imran; A. R., Othman (Universiti Malaysia Pahang, 2010)
Malaysian Technical Universities Conference on Engineering and Technology organized by Universiti Malaysia Pahang in collaboration with Universiti Tun Hussein Onn Malaysia, Universiti Teknikal Malaysia Melaka & Universiti Malaysia Perlis on June, 20th - 22nd, 2009, at MS Garden Hotel, Kuantan, Pahang, Malaysia.